2014
DOI: 10.3109/10837450.2014.892130
|View full text |Cite
|
Sign up to set email alerts
|

Brain-targeted delivery of doxorubicin using glutathione-coated nanoparticles for brain cancers

Abstract: We conclude that the initial in vitro characterization of the NPs demonstrates potential in delivering doxorubicin to cancer cells with possible future application in targeting brain cancers in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…GSH receptors at the BBB interface offer an option in targeting these receptors by GSH-coated nanoparticles to escalate the active or passive transcytosis of therapeutic agents to the brain [12,13]. GSH-PEGylated liposomes have been effectively applied as a brain drug delivery platform for the improvement of numerous treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSH receptors at the BBB interface offer an option in targeting these receptors by GSH-coated nanoparticles to escalate the active or passive transcytosis of therapeutic agents to the brain [12,13]. GSH-PEGylated liposomes have been effectively applied as a brain drug delivery platform for the improvement of numerous treatments.…”
Section: Discussionmentioning
confidence: 99%
“…GSH, an endogenous tripeptide, possesses a central nervous system (CNS) concentration up to 3 mM [12]. It has antioxidant-like characteristics and is readily transported across the BBB [13]. Recent reports have demonstrated that GSH can be used as a targeting ligand linked to PEGylated nanoparticles to improve delivery of therapeutics to CNS [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have underlined the importance of both astrocytes and endothelial cells to reproduce in vitro structural and functional characteristics of the BBB in vivo [ 16 , 31 – 36 ]. Since glial factors are well conserved among species, many heterologous models have been described so far [ 37 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 Many receptors are overexpressed on the brain cells such as the cloned μ opioid receptor, 6 the low-density lipoprotein receptor, 7 N -methyl- d -aspartate receptor, insulin receptor, 8 kinin-B2 receptors (BK-B2R), 9 angiotensin II AT1 and AT2 receptors, 10 and glutathione. 11 13 …”
Section: Introductionmentioning
confidence: 99%